1994
DOI: 10.1364/ao.33.001022
|View full text |Cite
|
Sign up to set email alerts
|

Fast-neutron radiation effects in a silica-core optical fiber studied by a CCD-camera spectrometer

Abstract: A simple CCD-camera spectrometer was deployed at the Los Alamos Spallation Radiation Effects Facility to characterize fast-neutron irradiation effects in several silica-based optical fibers over the wavelength range 450-1100 nm. The experimental arrangement allowed optical loss spectra to be developed from remotely recovered frame grabs at various times during irradiation without it being necessary to resort to cutback methods. Data recorded for a pure-silica-core/F-doped-silica-clad fiber displayed a peculiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Optical fibres have long been used as communication links in these environments [1] . Although radiation induced attenuation is observed, this can be counteracted by increasing power levels [2] . Wavelength encoded sensor technology i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Optical fibres have long been used as communication links in these environments [1] . Although radiation induced attenuation is observed, this can be counteracted by increasing power levels [2] . Wavelength encoded sensor technology i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies deal with radiation effects at low as well as moderate accumulated dose (see references in [1] and [2]). Fewer publications are available concerning high gamma dose and neutron fluence [3]- [8]. However, sensing capability and data transmission could be also conceived under intense radiation field, e.g., inside a fission reactor.…”
Section: Introductionmentioning
confidence: 99%
“…The stressed bonds which are the precursors to these sites result from three-or four-member ring structures in the silica matrix where the Si-O-Si bonds are not allowed to exist with their natural angle [4]. Previous work has shown that defects can be induced from stressed bonds through exposure to gamma rays [5,6] and high-energy particles [7] but also through one or two photon absorption occurring during the guidance of light from UV excimer lasers (KrF 248 m, ArF 193 nm, and F 2 157 nm) [8,9]. Other work has also been reported which demonstrates defect formation in bulk media due to few photon absorption from ultrashort, microjoule titanium sapphire laser pulses with high peak powers (50-300 MW) in the near infrared (800 nm) [10].…”
mentioning
confidence: 99%